EFFECTIVENESS OF BIO INSETICIDES FROM TOBACCO LEAVES AS A LARVACIDE OF Aedes aegypti MOSQUITO LARVAE - Astawa, I Made Mulya; Sudarmaja, I Made; Swastika, I Kadek; Diarthini, Ni Luh Eka (E-Jurnal Medika Udayana; Vol 14 No 2 (2025): E-Jurnal Medika Udayana, 2025)
Dengue infection is a group of diseases caused by dengue virus infection which is transmitted by the bite of Aedes Spp . In 2019, 138,127 Indonesians suffered from dengue infection and 919 of them died. Control with physical and chemical methods is considered still not able to eradicate dengue infection vectors, even chemical control causes resistance of Aedes Spp. larvae to temephos. Therefore, alternative natural pesticides are needed, one of which is tobacco plants. Tobacco plants contain many chemical compounds that are varied, effective, and biodegradable, so they should be considered as insecticides that are safe for the environment. The purpose of this study was to determine the effectiveness of tobacco leaves as larvicides in killing Aedes aegypti mosquito larvae. This research is classified as a pure experimental research (true experiment) with a post test only research design with a control group design. The sample used was the third instar Aedes aegypti mosquito larvae from the Parasitology Laboratory, Faculty of Medicine, Udayana University, which was then tested with a solution of tobacco leaf extract with concentrations of 100 ppm, 150 ppm, 200 ppm, 300 ppm, 400 ppm, and 500 ppm. The number of larvae was counted after 24 hours and repeated 4 times. The results of the probit analysis with a 95% confidence level showed that the LC50 value was at a concentration of 261.06 ppm and the LC90 value was at a concentration of 509.43 ppm. Tobacco leaf extract ( Nicotiana tabacum L. ) has a larvicidal effect on Aedes aegypti larvae with a concentration of 261.06 ppm capable of killing 50% of Aedes aegypti larvae for 24 hours.   Keywords: Tobacco, Larvicide, Aedes aegypti , Nicotiana tabacum L.